EKSISTENSI SUPREMUM DAN INFIMUM DENGAN TEOREMA CANTOR DEDEKIND - Bito, Nursiya (Jurnal Sainstek, 2010)
In this paper, we will try to proof existence of supremum and infimum with Cantor Dedekind theorem. Before we discuss this material, necessary to introduce several basic concepts, especially Cut Dedekind and Supremum and Infimum concepts. The method we are presenting here is due to Richard Dedekind (1831-1916) whose work entitled What are and what should be numbers?. Cantor Dedekind theorem very important to show that nothing gap at real numbers system.